'Then we were ready to be radicals!': school student activism in Finnish upper secondary schools in 1960–1967. Issue 3 (27th May 2021) - Jouhki, Essi
ABSTRACT: In the Western countries, Scandinavia and Finland included, the legacy of the student movement of the 1960s has been extensive and established a fixed narrative of a radical movement. This article challenges the elitist and university-centred grand narrative and argues that the student movement was more multifaceted and mobilized young people of various ages and backgrounds. This is done by addressing the international student movement from the perspective of school-aged students in Finnish upper secondary schools, focusing on student activism carried out in school-sanctioned student associations. Above all, this article aims to distinguish the relatively unknown history of the Scandinavian school student movement.